1970
DOI: 10.1080/00288233.1970.10425410
|View full text |Cite
|
Sign up to set email alerts
|

Embryo survival in mature Romney ewes relative to live weight and face cover

Abstract: In Experiment I fertilised eggs were transplanted at the rate of I, 2, or 4 per recipient ewe and these animals were autopsied in early pregnancy. In Experiment 2 ewes were mated to fertile rams and autopsied 18-30 days later. Some of these ewes had not conceived to egg transfer (Expt I).Transfer of I, 2, or 4 eggs did not affect the percentage of ewes which became pregnant. An ovum had a greater chance of surviving if transferred singly rather than as one of a multiple number of eggs.The number of corpora lut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…That live weight may influence embryo survival might be inferred from the reported increase in barrenness found in ewes of low live weight (Coop, 1962), from studies of Bennett et al (1964) and Edey (1970a, b) which both reported effects of undernutrition in light but not heavy ewes. Cumming & McDonald (1970) found no significant relationship between live weight and survival of transplanted ova in ewes of medium and high live weight. In the present study ewes of low live weight were not included and the study failed to confirm that live weight or body condition were important factors affecting embryo I .…”
Section: Embryo Survivalmentioning
confidence: 68%
“…That live weight may influence embryo survival might be inferred from the reported increase in barrenness found in ewes of low live weight (Coop, 1962), from studies of Bennett et al (1964) and Edey (1970a, b) which both reported effects of undernutrition in light but not heavy ewes. Cumming & McDonald (1970) found no significant relationship between live weight and survival of transplanted ova in ewes of medium and high live weight. In the present study ewes of low live weight were not included and the study failed to confirm that live weight or body condition were important factors affecting embryo I .…”
Section: Embryo Survivalmentioning
confidence: 68%
“…Coop (1964) also observed increased barrenness in ewes of low body weight. These observations have been challenged by Cockrem (1965), and Cumming and McDonald (1970) presented data that suggest no relationship between live weight at mating and the degree of embryonic loss.…”
Section: Discussionmentioning
confidence: 82%